Intersections of Gender, Class, and Culture in the Feminist Representation of Kretek Girl Series Episode 2 - Yuliwar, Yohanes Sonnie; Harahap, Halomoan (Universitas Pakuan, 2025)
This study explores the representation of feminism and gender power relations in Kretek Girl series episode 2 through a semiotic and feminist theoretical framework. Using John Fiske’s semiotic analysis combined with Laura Mulvey’s concept of the “male gaze” and bell hooks’ intersectionality theory, this research examines how female characters are portrayed in relation to patriarchy, class, and cultural context. The study employs a qualitative descriptive approach focusing on narrative structure, visual elements, dialogue, and character representation to uncover how signs construct feminist meanings within the story. The findings reveal that Kretek Girl presents a nuanced depiction of feminism, characterized by a tension between women’s resistance and patriarchal dominance. Female characters demonstrate agency and empowerment, yet remain constrained by social norms that reinforce gender hierarchies. The semiotic analysis highlights how visual and narrative codes—such as costume, body movement, and camera framing—reflect both subordination and subtle defiance against male-centered perspectives. Furthermore, intersectional aspects of class and culture shape different experiences of womanhood, emphasizing that feminism in Indonesian media operates through negotiation rather than confrontation. The study concludes that Kretek Girl contributes to the evolving discourse of feminist representation in Indonesian cinema by portraying women’s empowerment as a complex, layered process within a patriarchal society.